Perancangan Lengan Robot 5 Derajat Kebebasan Dengan Pendekatan Kinematika - - Firmansyah; Yuwaldi Away; Rizal Munadi; Muhammad Ikhsan; Ikram Muddin (Jurnal Rekayasa Elektrika, 2014)
This study discusses the design of arm robot model with 5 degree of freedom that is designed to be a small-scale model of the articulated robot industry to simulate the movement of the robots industry. The objective of this research is to build a real arm robot based on kinematic aspects with the movement of waist, shoulder, elbow, wrist pitch, wrist roll and gripper, and to analyze the robot movement. The design includes building the real arm robot based on Arduino Uno board controller and the movement of the robot using servo motor DC. The robot  can be controlled automatically from the computer with the RS-232 or USB port interface and it learns about the kinematic of the robot’s arm when an experiment on the forward kinematic is accomplished. The robot was running well, with the maximum distance that can be reached by the robot on the coordinate axis  x = 425 mm, y = 425 mm and  z = 480 mm.